Modelling Population Exposure to Traffic Air Pollution Using GIS - Jensen, Steen Solvang (Proceedings from the Annual Transport Conference at Aalborg University, 1996)
The paper outlines the background, methodology and perspectives for an ongoing Danish PhD project concerning exposure of the Danish population to traffic air pollution. The objective of the research project is to develop a model for population exposure to traffic induced air pollution in Denmark in order to improve assessment of the health impacts of traffic air pollution and the impact of various urban and traffic control strategies to reduce the population's exposure to traffic air pollution. Part of the project is to establish a population exposure model for an urban environment as a case study. The model will combine modelled air pollution data and population data using a Geographic Information System (ArcView). The air pollution will be modelled using the Danish Operational Street Pollution Model (OSPM). A simple population dynamics model will be established to model the number of people which simultaneously are present at a given area during a given time period. The project is a part of a PhD study funded by the Danish Transport Council and the Danish Research Academy. The study is appointed 2.5 years and terminates June 1997.